Novel chiral binaphthalene-linked pyrenes. Synthesis, structure, and spectroscopy. (June 2017) - Zheng, Yingting; Zhao, Luyang; Zhang, Yuehong; Wang, Chiming; Wang, Kang; Qi, Dongdong; Jiang, Jianzhuang
Abstract: Novel chiral pyrene-binaphthalene compounds, ( R )-/( S )-(13Z, 21bZ)-dinaphtho[2, 1-e:1′, 2′-g]pyreno[4, 5-b][1, 4]diazocine (1 ) and ( R )-/( S )-(3bZ, 5Z, 7Z, 9Z, 12bZ, 14Z, 16Z, 18Z)-bis(dinaphtho[2, 1-e:1′, 2′-g])pyreno[4, 5-b:9, 10-b′]bis([1, 4]diazocine) (2 ), were synthesized and characterized by a series of spectroscopic methods including MALDI-TOF mass, NMR, and electronic absorption methods. Their binaphthalene-linked pyrene nature has been unambiguously revealed on the basis of single crystal X-ray diffraction analysis of both ( R )- and ( S )-1 . In addition, their electronic structure was also investigated on the basis of DFT calculations. Graphical abstract: Highlights: Two novel chiral binaphthalene-linked pyrenes have been synthesized. The compounds exhibited impressive CD signal intensity. Orbital interaction between the binaphthalene group(s) and pyrene moiety was revealed.